2005
DOI: 10.1007/s00244-004-0041-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzymes and Tissue Regeneration in Eurythoe complanata (Polychaeta: Amphinomidae) Exposed to Used Vehicle Crankcase Oil

Abstract: Polychaetes, Eurythoe complanata, from the Gulf of Cariaco,Venezuela, were exposed to 0.3, 1.6, and 3.3% water-soluble fraction (WSF) of used crankcase oil during 15 and 21 days. The antioxidant enzymes glutathione peroxidase (GPX), glutathione reductase (GR), catalase (CAT), and glutathione-S-transferase (GST) were assayed in the body wall tissue. Furthermore, after chemical exposure, the polychaetes were cut into equal halves; then wound healing and the number of regenerated body segments were recorded perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 31 publications
1
10
0
3
Order By: Relevance
“…A similar result was also found when P. aibuhitensis was exposed to Pb 2+ (Tian et al 2014). Previous studies have suggested that CAT activity increases when living organisms suffer toxic oxidative stress (Nusetti et al 2005, Tian et al 2014). In our study, increased CAT activity was found at 12 h of exposure, which possibly counterbalanced sulphide-induced ROS production.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A similar result was also found when P. aibuhitensis was exposed to Pb 2+ (Tian et al 2014). Previous studies have suggested that CAT activity increases when living organisms suffer toxic oxidative stress (Nusetti et al 2005, Tian et al 2014). In our study, increased CAT activity was found at 12 h of exposure, which possibly counterbalanced sulphide-induced ROS production.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, we inferred that SOD neutralized ROS instead of CAT at this time. Nusetti et al (2005) also found that the existence of other enzymatic and nonenzymatic antioxidants played a function in stead of GSH activity, which could be influenced by glutathione reductase (GR) activity. CAT activity in all treatments was lower than that in the control during the initial 6 h of the recovery period, which seemed to be an extension of those at 96 h exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, en el músculo blanco del pez Mullus barbatus, las enzimas SOD y GST incrementan sus actividades en invierno, y CAT, GR y GPx en primavera (Mathieu et al 1991, Pavloviae et al 2009). Existe complejidad en la interpretación de la actividad de las enzimas antioxidantes, ya que también pueden observarse niveles elevados en presencia de contaminantes (Nusetti et al 2005, Zapata-Vívenes et al 2005.…”
Section: Discussionunclassified
“…E. complanata es una especie que ha sido utilizada como modelo biológico en la estandarización de protocolos ecotoxicológicos, a través de biomarcadores moleculares y celulares (sistema inmune y antioxidante, poder de regeneración de tejidos, y la capacidad corporal de acumular xenobióticos) aplicados a la evaluación de sedimentos marino-costeros impactados por contaminantes (Méndez & Páez-Osuna 1998, Nusetti et al 1998, 2005Zapata-Vívenes et al 2005, Vásquez-Núñez et al 2007. Sin embargo, no existe información sobre sus respuestas bioquímicas basales mediadas por los cambios ambientales, en especialmente la temperatura.…”
Section: Introductionunclassified
“…Following removal of only the asegmental region, regeneration of the prostomium has been documented in several species of Erséus and Källersjö (2004), Struck et al (2007), Struck et al (2011), andWeigert et al (2014). Regeneration data are from Morgulis (1909), Cresp (1952), Olive and Moore (1975), Nusetti et al (2005), Hentschel and Harper (2006), and Giani et al (2011) or are reviewed in Hyman (1940), Berrill (1952, Herlant-Meewis (1964), Bely (2006Bely ( , 2010. AR -anterior regeneration; PR -posterior regeneration. naidid clitellates (including one that cannot regenerate segments), but fails to occur in at least one species of naidid, two species of dorvilleid, and one species of nereid (Pfannenstiel, 1973(Pfannenstiel, , 1974Bely and Sikes, 2010a).…”
Section: Annelidamentioning
confidence: 99%